From replication to substantiation: A complexity theory perspective. (April 2023) - Al-Hoorie, Ali H.; Hiver, Phil; Larsen-Freeman, Diane; Lowie, Wander
Abstract: In contemporary methodological thinking, replication holds a central place. However, relatively little attention has been paid to replication in the context of complex dynamic systems theory (CDST), perhaps due to uncertainty regarding the epistemology–methodology match between these domains. In this paper, we explore the place of replication in relation to open systems and argue that three conditions must be in place for replication research to be effective: results interpretability, theoretical maturity, and terminological precision. We consider whether these conditions are part of the applied linguistics body of work, and then propose a more comprehensive framework centering on what we call substantiation research, only one aspect of which is replication. Using this framework, we discuss three approaches to dealing with replication from a CDST perspective theory. These approaches are moving from a representing to an intervening mindset, from a comprehensive theory to a mini-theory mindset, and from individual findings to a cumulative mindset.